Breast self-examination practice among women in Africa: a systematic review and Meta-analysis - Wubareg Seifu; Liyew Mekonen (BMC, 2021)
Abstract Background In resource limited countries breast self-examination has been recommended as the most appropriate method for early detection of breast cancer. Available studies conducted on breast self-examination practice in Africa currently are inconsistent and inclusive evidences. On top of that the available studies are unrepresentative by regions with small sample size. Therefore, this systematic review and meta-analysis were conducted to summarize and pool the results of individual studies to produce content level estimates of breast self-examination practice in Africa. Methods A systematic review and meta-analysis were done among studies conducted in Africa using Preferred Item for Systematic Review and Meta-analysis (PRISRMA) guideline. Studies were identified from PubMed, Google Scholar, HINARI, EMBASE, CINAHL, Cochrane, African Journals Online and reference lists of identified prevalence studies. Unpublished sources were also searched to retrieve relevant articles. Critical appraisal of studies was done through Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument (JBI-MAStARI). The meta-analysis was conducted using STATA 13 software. Heterogeneity was assessed using I2 statistics while publication was assessed through funnel plot. Forest plot were used to present the pooled prevalence with a 95% confidence interval (CI) using the random effect model. Results In this meta-analysis 56 studies were included with a total of 19, 228 study participants. From the included studies 25(44.64%) were from West Africa, 22(39.29%) East Africa, 5(8.93%) North Africa, 3(5.36%) Central Africa and 1(1.79%) South Africa. The overall pooled prevalence of ever and regular breast self-examination practice in Africa was found to be 44.0% (95% CI: 36.63, 51.50) and 17.9% (95% CI: 13.36, 22.94) respectively. In the subgroup analysis there was significant variations between sub regions with the highest practice in West Africa, 58.87% (95 CI%: 48.06, 69.27) and the lowest in South Africa, 5.33% (95 CI%: 2.73, 10.17). Conclusion This systematic review and meta-analysis revealed that breast self-examination practice among women in Africa was low. Therefore, intensive behavioral change communication and interventions that emphasize different domains should be given by stakeholders. PROSPERO registration number CRD42020119373.